Predicting citizens’ support for surveillance cameras. Does police legitimacy matter? - Gurinskaya, Anna (International journal of comparative and applied criminal justice, 2020)
The paper examines factors that shape citizens’ attitudes towards closed-circuit television (CCTV) cameras in public places. Using survey data from 570 university students from St.Petersburg (Russia), we show that the majority of young people approve the use of cameras for surveillance in public spaces. Findings suggest that males hold amore negative view towards cameras compared to females, while income, victimization status, and perceived level of disorder do not predict support for cameras. However, fear of crime, privacy considerations, and police legitimacy are all strongly related to cameras’ acceptance. Further, trust in the effectiveness of surveillance technology partially mediates the effect of these factors and predicts a higher level of acceptance. Findings have important implications for improving police-citizen relations and building a foundation for effective security coproduction in the new digital age.